Apparent calcium dependence of vesicle recruitment. (7th August 2018) - Ritzau‐Jost, Andreas; Jablonski, Lukasz; Viotti, Julio; Lipstein, Noa; Eilers, Jens; Hallermann, Stefan
Abstract : Key points: Synaptic transmission relies on the recruitment of neurotransmitter‐filled vesicles to presynaptic release sites. Increased intracellular calcium buffering slows the recovery from synaptic depression, suggesting that vesicle recruitment is a calcium‐dependent process. However, the molecular mechanisms of vesicle recruitment have only been investigated at some synapses. We investigate the role of calcium in vesicle recruitment at the cerebellar mossy fibre to granule cell synapse. We find that increased intracellular calcium buffering slows the recovery from depression following physiological stimulation. However, the recovery is largely resistant to perturbation of the molecular pathways previously shown to mediate calcium‐dependent vesicle recruitment. Furthermore, we find two pools of vesicles with different recruitment speeds and show that models incorporating two pools of vesicles with different calcium‐independent recruitment rates can explain our data. In this framework, increased calcium buffering prevents the release of intrinsically fast‐recruited vesicles but does not change the vesicle recruitment rates themselves. Abstract: During sustained synaptic transmission, recruitment of new transmitter‐filled vesicles to the release site counteracts vesicle depletion and thus synaptic depression. An elevated intracellular Ca 2+ concentration has been proposed to accelerate the rate of vesicle recruitment at many synapses. This conclusion is often based on the finding that increased intracellular Ca 2+ buffering slows the recovery from synaptic depression. However, the molecular mechanisms of the activity‐dependent acceleration of vesicle recruitment have only been analysed at some synapses. Using physiological stimulation patterns in postsynaptic recordings and step depolarizations in presynaptic bouton recordings, we investigate vesicle recruitment at cerebellar mossy fibre boutons. We show that increased intracellular Ca 2+ buffering slows recovery from depression dramatically. However, pharmacological and genetic interference with calmodulin or the calmodulin–Munc13 pathway, which has been proposed to mediate Ca 2+ ‐dependence of vesicle recruitment, barely affects vesicle recovery from depression. Furthermore, we show that cerebellar mossy fibre boutons have two pools of vesicles: rapidly fusing vesicles that recover slowly and slowly fusing vesicles that recover rapidly. Finally, models adopting such two pools of vesicles with Ca 2+ ‐independent recruitment rates can explain the slowed recovery from depression upon increased Ca 2+ buffering. Our data do not rule out the involvement of the calmodulin–Munc13 pathway during stronger stimuli or other molecular pathways mediating Ca 2+ ‐dependent vesicle recruitment at cerebellar mossy fibre boutons. However, we show that well‐established two‐pool models predict an apparent Ca 2+ ‐dependence of vesicle recruitment. Thus, previous conclusions of Ca 2+ ‐dependent vesicle recruitment based solely on increased intracellular Ca 2+ buffering should be considered with caution. Key points: Synaptic transmission relies on the recruitment of neurotransmitter‐filled vesicles to presynaptic release sites. Increased intracellular calcium buffering slows the recovery from synaptic depression, suggesting that vesicle recruitment is a calcium‐dependent process. However, the molecular mechanisms of vesicle recruitment have only been investigated at some synapses. We investigate the role of calcium in vesicle recruitment at the cerebellar mossy fibre to granule cell synapse. We find that increased intracellular calcium buffering slows the recovery from depression following physiological stimulation. However, the recovery is largely resistant to perturbation of the molecular pathways previously shown to mediate calcium‐dependent vesicle recruitment. Furthermore, we find two pools of vesicles with different recruitment speeds and show that models incorporating two pools of vesicles with different calcium‐independent recruitment rates can explain our data. In this framework, increased calcium buffering prevents the release of intrinsically fast‐recruited vesicles but does not change the vesicle recruitment rates themselves.